Novel poppular dan kecenderungan khalayak remaja - Mawar Safei,; Rosnah Baharudin,; Siti Rugayah Tibek,; Fariza Md Sham,; Zamri Ariffin,; Samsiah Mohd Nor, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
This study is based on the FRGS fund titled UKM-PP-04-FRGS0004-2006 iaitu “Citra Dakwah dalam Novel Melayu Popular: Kajian Pandangan dan Kecenderungan Pembaca Remaja” (Dakwah Images in Popular Malay Novels: Study on the Views and Tendency in Adolescent Readers”. This research focus on what popular novels had offered to the acceptance among most of the adolescent readers. The most five popular novels are Bicara Hati (Damya Hana), Kau Untukku (Aisya Sofea), Jendela Hati (Aisya Sofea), Kau yang Satu (Nia Azalea) dan Manisnya Cinta (Anis Ayuni). The findings discover that there are two aspects which influence on the scenario e.g. (i) the external which involves publishers, promotions, authors and special package in novels; (ii) the internal which includes themes/problems, characters/characteristics and writing techniques. The 4Ps external traits give such an impact on this genre. Whilst the internals fortify via the love theme, marriage and family conflict; attractive, well educated, urban stylish characters; straightforward plot with coincidences; colloquial style especially jumbling Malay and English. All these traits go well with the adolescents that favor simplicity and pleasure